The potential of brick waste as fine aggregate replacement in concrete production - Muhammad Saufi, Ishak (2014)
This study is focusing on determining the suitability of brick waste as the fine aggregate replacement in concrete production. The fine aggregate in concrete was replaced by using brick waste with various different proportions The performance of concrete with brick waste in the mixture were compared with the conventional concrete with grade C25. 55 cubes and 10 beams including control samples were prepared for this study. The water cement ratio 0.45 were standardize in all concrete samples. Brick waste from construction were crushed to be added in concrete mixture to replace fine aggregate with different proportions of 0%, 5%, 10%, 15%, and 20%. Four types of laboratory tests; slump test, compressive strength test, flexural test and water penetration test were conducted to achieve the objective of the study. The results obtained from the laboratory test shows that the replacement proportion 10% of clay brick waste in concrete were enhancing the strength and durability of the concrete. The workability and water penetration of the concrete also were following the specified standard. Therefore, it is proven that the replacement by proportion of brick waste in concrete production is suitable.